2012
DOI: 10.1155/2012/656340
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 2 in Cancer-Induced Immune Suppression

Abstract: Inhibitory molecules of the B7/CD28 family play a key role in the induction of immune tolerance in the tumor microenvironment. The programmed death-1 receptor (PD-1), with its ligands PD-L1 and PD-L2, constitutes an important member of these inhibitory pathways. The relevance of the PD-1/PD-L1 pathway in cancer has been extensively studied and therapeutic approaches targeting PD-1 and PD-L1 have been developed and are undergoing human clinical testing. However, PD-L2 has not received as much attention and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
250
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(257 citation statements)
references
References 74 publications
5
250
0
2
Order By: Relevance
“…Differences may be attributed to the specificity of avelumab for PD‐L1, which leaves PD‐L2/PD‐1 interactions intact and allows for maintenance of immune homeostasis18, 19; however, additional evidence is required to fully understand the contribution of PD‐L2. Furthermore, differences in study design, eligibility criteria, and methodology for defining irAEs may account for variations in incidences across trials of ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Differences may be attributed to the specificity of avelumab for PD‐L1, which leaves PD‐L2/PD‐1 interactions intact and allows for maintenance of immune homeostasis18, 19; however, additional evidence is required to fully understand the contribution of PD‐L2. Furthermore, differences in study design, eligibility criteria, and methodology for defining irAEs may account for variations in incidences across trials of ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cho, J. Koh, D.H. Chung, H. Go, manuscript submitted for publication) revealed that PD-L2 expression in primary CCRCC was associated with LN metastasis and poor prognosis. Both PD-L1 and PD-L2 are expected to play a key role in cancer-induced immune suppression in the tumor microenvironment [26,27]. However, Ghiotto et al [28] showed that PD-L1 interacts with not only PD-1 but also CD80, and significant conformational changes occur upon PD-L1/PD-1 interaction, which is not the case for PD-L2/PD-1 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ghiotto et al [28] showed that PD-L1 interacts with not only PD-1 but also CD80, and significant conformational changes occur upon PD-L1/PD-1 interaction, which is not the case for PD-L2/PD-1 interaction. Furthermore, PD-L1 competes with PD-L2 for PD-1 binding.The affinity of PD-L2 to PD-1 is much higher than that to PD-L1, but PD-L2 expression is more dependent on environmental cues than PD-L1 [27].Thus, it is possible that the effects of PD-L1 and PD-L2 expression on TKI responsiveness and prognosis could be distinct.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is broadly expressed in immune and nonimmune cells, whereas PD-L2 expression is limited to activated macrophages, suggesting that PD-L1 plays an important role in peripheral immune tolerance. [6][7][8]12 During chronic viral infection, interaction between PD-1 and PD-L1 or PD-L2 leads to T-cell exhaustion that is reversed by blockade of PD-1 or programmed cell death-1 ligands (PD-Ls). 6,8,13 Furthermore, PD-1 + T cells were observed in tumor tissues and were functionally impaired upon engagement by PD-L1 or PD-L2.…”
mentioning
confidence: 99%